Acceptability of a 'treat to target' approach in inflammatory bowel disease to patients in clinical remission. Issue 1 (24th January 2020) - Selinger, Christian; Carbonell, Jenelyn; Kane, John; Omer, Mandour; Ford, Alexander Charles
Abstract : Background: A 'treat to target' approach aiming for remission of clinical symptoms and absence of mucosal inflammation has been proposed in inflammatory bowel disease (IBD). We aimed to establish whether patients with IBD in clinical remission find this approach acceptable. Methods: Patients in glucocorticosteroid-free clinical remission underwent a face-to-face structured, quantitative interview and rated the acceptability of treat to target on a 10-point Likert scale. We analysed factors associated with agreement to treat to target. Results: The cohort comprised 298 patients (144 Crohn's disease, 136 ulcerative colitis, 18 IBD-unclassified). Elevated C-reactive protein was found in 24.4% and elevated faecal calprotectin in 17.7%. Overall, 66.2% of patients rated a treat to target approach as acceptable (Likert scale ≥8). Acceptable treatment aims for patients were avoidance of flare, hospitalisation, surgery and colorectal cancer. Using binary logistic regression analysis the following were not predictive of accepting a treat to target approach: age, diagnosis, disease phenotype, surgical history, disease duration, patient knowledge, adherence, anxiety, depression and patient-reported control of disease. Better adherence to current therapy was associated with accepting a treat to target approach (B=0.16, p=0.039). Conclusion: In a cohort of patients in clinical remission, where this strategy is most relevant, two-thirds of patients agreed with treat to target. Patients with better current adherence were more likely to accept treat to target. Patient education and counselling materials will need to be developed to convince a substantial minority of patients of the importance of treat to target.